Design of Tunable Optical Band Pass Filter based on in-Line PM-Mach Zehnder Interferometer - Mutar, Baraa H; Mansour, Tahreer S. (Iraqi Journal of Laser, 2021)
In this paper, tunable optical band-pass filters based on Polarization Maintaining Fiber –Mach Zehnder Interferometer presented. Tunability of the band-pass filter implemented by applying different mechanical forces N on the micro-cavities splicing regions (MCSRs). The micro-cavity formed by using three variable-lengths of single-mode polarization-maintaining fiber with (8, 16, 24) cm lengths, splice between two segments of (SMF-28) with (26, 13) cm lengths, using the fusion splicing technique.  Ellipsoidal shape micro-cavities experimentally achieved parallel to the propagation axis having dimensions between (12-24) μm of width and   (4-12) μm of length. A micro-cavity with width and length as high as 24 μm and 12 μm have higher sensitivity of 0.00115 μԐ when 0.098 N applied to the micro-cavity splicing region. And full width half maximum was obtained  251.584 pm when polarization-maintaining fiber length was  16 cm after applied 0.49N on the micro-cavity splicing region. The pulsed laser source used in this experiment has peak power 1.2297mW, 286 pm spatial FWHM, and centered at 1546.7 nm.